RIF1 Links Replication Timing with Fork Reactivation and DNA Double-Strand Break Repair - Janusz Blasiak (MDPI AG, 2021)
Replication timing (RT) is a cellular program to coordinate initiation of DNA replication in all origins within the genome. RIF1 (replication timing regulatory factor 1) is a master regulator of RT in human cells. This role of RIF1 is associated with binding G4-quadruplexes and changes in 3D chromatin that may suppress origin activation over a long distance. Many effects of RIF1 in fork reactivation and DNA double-strand (DSB) repair (DSBR) are underlined by its interaction with TP53BP1 (tumor protein p53 binding protein). In G1, RIF1 acts antagonistically to BRCA1 (BRCA1 DNA repair associated), suppressing end resection and homologous recombination repair (HRR) and promoting non-homologous end joining (NHEJ), contributing to DSBR pathway choice. RIF1 is an important element of intra-S-checkpoints to recover damaged replication fork with the involvement of HRR. High-resolution microscopic studies show that RIF1 cooperates with TP53BP1 to preserve 3D structure and epigenetic markers of genomic loci disrupted by DSBs. Apart from TP53BP1, RIF1 interact with many other proteins, including proteins involved in DNA damage response, cell cycle regulation, and chromatin remodeling. As impaired RT, DSBR and fork reactivation are associated with genomic instability, a hallmark of malignant transformation, RIF1 has a diagnostic, prognostic, and therapeutic potential in cancer. Further studies may reveal other aspects of common regulation of RT, DSBR, and fork reactivation by RIF1.